LITERATURE REVIEW STUDY: THE ROLE OF HUMAN RESOURCE PLANNING (HRP) IN IMPROVING COMPANY PERFORMANCE - Putri Latifah Anum; Ritha F Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research was conducted to find out the role of Human Resource Planning (HRP) in improving company performance. Human Resource Planning is a technique used to explore and organize potential, competencies, skills, talents, etc. Therefore, companies need Human Resource Planning to operate and maintain the company to continue to exist. The importance of Human Resource Planning in a company must be the main issue when a company wants to continue to exist and be sustainable because every company throughout the world needs good human resource planning so that it will affect the company's performance, in other words good Human Resource Planning will improve the company's performance.